2019
DOI: 10.1093/jac/dkz273
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the lymphoid tissue bioavailability of antiretrovirals in human primary lymphoid endothelial cells and in mice

Abstract: Background The secondary lymphoid tissues (LTs), lymph nodes (LNs) and gut-associated lymphoid tissue (GALT) are considered reservoirs for HIV. Antiretrovirals (ARVs) have lower penetration into LT. In vitro models predictive of ARV LT penetration have not been established. Objectives To develop an in vitro model of LT bioavailability using human lymphoid endothelial cells (HLECs) and investigate its predictability with in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
4
22
0
Order By: Relevance
“…We suggest this might be due to diminished drug pressure on either tissue or cellular reservoirs. Indeed, it has been shown that INSTI diffusion in lymph nodes, with the exception of Elvitegravir, is generally poor ( 27 ), thus potentially exposing the virus to sub-optimal concentrations of antiretroviral compounds in this reservoir. Besides, the fact that the percentage of patients with VLLV increased after cART simplification could be in favor of an association between immune activation and poorer pharmacological control in reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest this might be due to diminished drug pressure on either tissue or cellular reservoirs. Indeed, it has been shown that INSTI diffusion in lymph nodes, with the exception of Elvitegravir, is generally poor ( 27 ), thus potentially exposing the virus to sub-optimal concentrations of antiretroviral compounds in this reservoir. Besides, the fact that the percentage of patients with VLLV increased after cART simplification could be in favor of an association between immune activation and poorer pharmacological control in reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…PHHs were treated with rifampin, rifabutin and rifapentine at 10 µM concentration for 72 h. with the corresponding untreated (negative) and 0.0025% methanol (vehicle) treated controls. We measured intracellular concentrations (ICC) of parent and des-acetyl-metabolites by liquid chromatography tandem mass spectroscopy (LC-MS/MS) as we have previously described [45][46][47][48][49] .…”
Section: Materials and Methods Primary Human Hepatocytes (Phhs)mentioning
confidence: 99%
“…Finally, Dyavar et al . examined LN tissue from mice dosed with dolutegravir and found a penetration ratio (PR) of 0.08, suggesting poor penetration; however, human LN data are not available for this INSTI 45 …”
Section: Pharmacology In the Hiv Reservoirmentioning
confidence: 98%
“…44 Finally, Dyavar et al examined LN tissue from mice dosed with dolutegravir and found a penetration ratio (PR) of 0.08, suggesting poor penetration; however, human LN data are not available for this INSTI. 45 Data regarding concentrations of LRAs in the LNs are minimal. Rosen et al examined panobinostat by mass spectrometry imaging in the LNs of three NHPs chronically infected with SIV and suppressed on ART.…”
Section: Lymph Nodesmentioning
confidence: 99%